Rapid detection of Heterobasidion annosum using a loop-mediated isothermal amplification assay - Hong-min, Zhou; Jian, Yu; Ying, Liu; Yuan, Yuan; Cui-ping, Wu; Yu-cheng, Dai; Jia-jia, Chen (Frontiers in Cellular and Infection Microbiology, 2023)
Heterobasidion annosum is one of the most aggressive pathogens of Pinus forests in Europe, causing considerable economic losses. To detect H. annosum for disease diagnosis and control, we developed a loop-mediated isothermal amplification (LAMP) reaction with a primer set designed from the glyceraldehyde 3-phosphate dehydrogenase (GAPDH) DNA sequences of H. annosum. In our study, this LAMP assay was found to be capable of efficiently amplifying the target gene within 60 min at 63°C. In specificity tests, H. annosum was positively detected, and other species were negative. The detection limit of this assay was found to be 100 pg·μL-1, and the assay was also successfully tested for use with basidiospore suspensions and wood samples. This study provides a rapid method for diagnosing root and butt rot caused by H. annosum, which will be of use in port surveillance of logs imported from Europe.